Inhibition of HDAC6 Attenuates Diabetes-Induced Retinal Redox Imbalance and Microangiopathy - Hossameldin Abouhish; Menaka C. Thounaojam; Ravirajsinh N. Jadeja; Diana R. Gutsaeva; Folami L. Powell; Mohamed Khriza; Pamela M. Martin; Manuela Bartoli (MDPI AG, 2020)
We investigated the contributing role of the histone deacetylase 6 (HDAC6) to the early stages of diabetic retinopathy (DR). Furthermore, we examined the mechanism of action of HDAC6 in human retinal endothelial cells (HuREC) exposed to glucidic stress. Streptozotocin-induced diabetic rats (STZ-rats), a rat model of type 1 diabetes, were used as model of DR. HDAC6 expression and activity were increased in human diabetic postmortem donors and STZ-rat retinas and were augmented in HuREC exposed to glucidic stress (25 mM glucose). Administration of the HDAC6 specific inhibitor Tubastatin A (TS) (10 mg/kg) prevented retinal microvascular hyperpermeability and up-regulation of inflammatory markers. Furthermore, in STZ-rats, TS decreased the levels of senescence markers and rescued the expression and activity of the histone deacetylase sirtuin 1 (SIRT1), while downregulating the levels of free radicals and of the redox stress markers 4-hydroxynonenal (4-HNE) and nitrotyrosine (NT). The antioxidant effects of TS, consequent to HDAC6 inhibition, were associated with preservation of Nrf2-dependent gene expression and up-regulation of thioredoxin-1 activity. In vitro data, obtained from HuREC, exposed to glucidic stress, largely replicated the in vivo results further confirming the antioxidant effects of HDAC6 inhibition by TS in the diabetic rat retina. In summary, our data implicate HDAC6 activation in mediating hyperglycemia-induced retinal oxidative/nitrative stress leading to retinal microangiopathy and, potentially, DR.